Naḥwa Mustaqbal Afḍal: Taʾammulāt fī Tafʿīl ʿAmaliyyat Taʿlīm al-Lughah al-ʿArabiyyah li-Abnāʾ Indūnīsiyā - Dihyatun Masqon (Department of Arabic Teaching, Faculty Tarbiyah, Universitas Darussalam Gontor, 2014)
Language is one of the greatest means through which people communicate, cooperate, and build relationships with others. Beyond serving as a tool of communication, it is also an instrument for thinking, expressing ideas, emotions, and experiences, preserving human knowledge, and transmitting cultural and civilizational heritage. Furthermore, language functions as a fundamental medium for teaching and learning. The Arabic language, in particular, serves as a gateway to Arab and Islamic culture and civilization. Teaching Arabic to non-native speakers requires specialized instructional methods that address the learners’ linguistic and cultural backgrounds, especially in the Indonesian context. In Indonesia, two major educational approaches have emerged in Arabic language instruction: the classical approach and the modern approach, each offering distinctive methods and innovations in teaching Arabic. This article reflects on the importance of strengthening Arabic language education for Indonesian learners by considering these educational approaches and their contributions to improving the quality of Arabic language instruction.